2018
DOI: 10.7874/jao.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Bilateral External Auditory Canal Pyogenic Granuloma in a Pregnant Woman

Abstract: A pyogenic granuloma is one of the most common benign tumors in the head and neck. However, it rarely occurs in the external auditory canal (EAC). We report a case of a pyogenic granuloma that involved the both EAC in a pregnant woman. The clinical manifestation is discussed with a literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…Further there was history of ear pricking in the past and histopathologic findings of haemangioma. Hence it was concluded that it was a case of acquired lesion which was a haemangioma in accordance with findings of Song K et al 7 Such small lesions in accessible areas have to be dealt with simple excision only. Further the findings on histopathological examination confirms the age old principle that any excisional biopsy must be sent for histopathologic characterization.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Further there was history of ear pricking in the past and histopathologic findings of haemangioma. Hence it was concluded that it was a case of acquired lesion which was a haemangioma in accordance with findings of Song K et al 7 Such small lesions in accessible areas have to be dealt with simple excision only. Further the findings on histopathological examination confirms the age old principle that any excisional biopsy must be sent for histopathologic characterization.…”
Section: Discussionsupporting
confidence: 79%
“…The tumor etiology remains uncertain but may involve frequent ear-picking and changes in hormone levels. 7 Rachappa MM et al, have written in their study that haemangiomas occur in skin of 4-10% of Caucasian new born with 3-to 5-fold greater incidence in females and also admitted that differentiation between a capillary haemangioma and pyogenic granuloma is somewhat unclear at this time. 8 Mills SE et al, suggested that the scientifically accurate term for pyogenic granuloma is the lobular capillary haemangioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these have the histologic similarities of capillary hemangioma [ 7 ]. However, pyogenic granuloma shows proliferation in lobules and predominant perithelial characteristics, rather than endothelial characteristics [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiologies of pyogenic granuloma are unclear, the factors of female sex hormones, chronic irritation, and trauma may have a risk to its development. 1-3 Excisional surgery is suggested, but cryosurgery, laser surgery, and electrodissection are recommended to avoid scar formation and deformity. 1…”
Section: Clinical Imagementioning
confidence: 99%